Development of conveyor for lab scale combustion chamber (palm shell feed analysis) / Abdul Aziz Ibrahim - Ibrahim, Abdul Aziz (2005)
The Project of 'Development of Conveyor for Palm Shell' has been carried out by the final year students of Bachelor of Engineering (Hons.) Mechanical, under the supervision of Mr. Wan Ahmad Najmi Bin Wan Mohamed. The project aimed to develop a practical conveyor for transporting palm shell into designed combustion chamber for research and evaluation, and also acts as a platform in order to give uniform capacity and suitable feed rate of palm shell into combustion chamber for combustion process. The development included three stages, namely design, fabricated and testing. The conveyor is inclined belt conveyor type and was made using rough top belt as its transporting belt. Results from the test using palm shell as a fuel showed reliable performance confirming with the design specification with some areas for further improvements.